Transverse mode instability of fiber oscillators in comparison with fiber amplifiers. (12th April 2018) - Hejaz, Kamran; Shayganmanesh, Mahdi; Azizi, Saeed; Abedinajafi, Ali; Roohforouz, Ali; Rezaei-Nasirabad, Reza; Vatani, Vahid
Abstract: Transverse mode instability (TMI) is experimentally investigated in a fiber oscillator and a fiber amplifier. For a reasonable comparison of TMI in these two configurations, the same optical components and design parameters are applied to both. Our experimental results show that the TMI power threshold in a fiber oscillator is lower than in a corresponding fiber amplifier. By using simulation software, a fiber oscillator and an amplifier are designed with similar characteristics, to provide identical conditions for all effective parameters on TMI in both of them. Since the signal propagation in fiber oscillators is different from that of single-pass fiber amplifiers, and also since both forward and backward propagating signals in fiber oscillators can generate thermo-optic index gratings, the observed lower TMI threshold in the fiber oscillator is due to its different interaction of light with index gratings.